Clinical best practices in optimal monitoring, early diagnosis, and effective management of antibody–drug conjugate-induced interstitial lung disease or pneumonitis: a multidisciplinary team approach in Singapore. (2nd December 2022) - Yong, Wei Peng; Teo, Felicia SW; Teo, Lynette LS; Ng, Matthew CH; Tan, Tira J.; Low, Su Ying; Wong, Karmen; Ang, Peter; Choo, Su Pin; Lee, Kim Hua; Lee, Soo Chin
ABSTRACT: Introduction: Interstitial lung disease (ILD) or pneumonitis remains an important adverse event identified with treatment with antibody–drug conjugates (ADCs). Drug-induced ILD (DILD) accounts for 3%–5% of common ILD cases and is a significant problem in clinical practice. Hence, with the anticipation of the widespread use of ADCs, it will be important for guidelines and recommendations to be established to direct and standardize the management of DILD by a multidisciplinary team (MDT). Areas covered: A thorough literature search was conducted using PubMed to identify relevant articles related to ADCs published between 1 January 2010 and 31 November 2022. Based on the review of the literature combined with expert opinions, this review article offers an overview of incidences of ILDs associated with the use of newer anticancer therapies, specifically ADCs, and discusses local-regional best practices in optimal monitoring, early diagnosis, and management of DILD involving an MDT. Expert opinion: Multidisciplinary input and consensus are crucial in the accurate diagnosis of DILD. The core group of essential attendees in the MDT are oncologists, pulmonologists, thoracic radiologists, and pathologists. This allows for the integration of expertise from different specialists to achieve a 'best fit' diagnosis and management.